Strategi Msdm dan Peran Motivasi Kerja dalam Meningkatkan Kinerja Pegawai Puskesmas: Literarure Review Manajemen SDM - Sabita Hasna Alifianti, Sabita Hasna Alifianti; Cecep Hermana (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the relationship between Human Resource Management (HRM) strategies and work motivation in improving employee performance at a Community Health Center (Puskesmas). The research method used was a literature review with a qualitative approach, examining various sources, such as national and international books and journals, related to HRM strategies, work motivation, and employee performance. The results indicate that implementing HRM strategies, including selective recruitment, continuous training, and fair performance appraisals, can create a work environment that supports employee work motivation. High work motivation, especially intrinsic motivation, has a positive impact on improving employee performance, loyalty, and engagement in achieving organizational goals. The conclusion of this study states that appropriate HRM strategies and the role of effective work motivation are key factors in creating optimal employee performance at Puskesmas. Therefore, it is important to continue developing innovative strategies and appropriate motivational programs to support public health services.   Keywords: Human Resource Management, Work Motivation, Employee Performance